Assessment of the Hydroelectricity Generation Potential of Gwaigwaye Reservoir in Funtua, Katsina State, Nigeria. - Olabisi, P. O.; Abdullahi, M. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Access to quality and adequate supply of electricity is one of the major challenges hampering development in Sub-Saharan Africa. Funtua as the industrial, commercial, and agricultural hub of Katsina State, Nigeria, needs to overcome the problem of epileptic power supply from the national grid. This study explored the hydro generation potential of Gwaigwaye Reservoir, the largest water resource in the area, by evolving a hydrological profile using water surface area in absence of flow gauging data. It also outlined from analysis, the technical requirements for hydroelectricity generation from the reservoir. Consequently, it was discovered from analysis that the average discharge obtainable is 18.54 m3/s. This would flow through four bulb turbines of 750 rpm speed to generate 17.8 MW of power or 14.033 GWh of energy in a year. It is therefore recommended that the Government of Katsina State should seek to implement this project for its potential to improve the living conditions and economy of the people of Funtua, the surrounding communities and the State.